Manufacture, characterisation and analytical application of nanomaterials in sensor devices - Ajaero, Chukwuemeka (2010)
The main objective of this study consisted of developing a new type of amperometric sensors based on depositing gold nanoparticles obtained from two different synthetic routes (thermal and ultrasonic methods) on the surface of a Sonogel Carbon matrix, in order to build electrochemical devices.